Three new species of agathotanaids (Tanaidacea: Paratanaoidea: Tanaidomorpha) from the lower bathyal zone off southwestern Java, Indonesia, Indian Ocean with notes on the global distribution and diversity of Agathotanaidae - Chim, C. K.; Tong, Samantha J. W. (Zootaxa, 2021)
Three new species of agathotanaids belonging to the genera Agathotanais, Bunburia and Paranarthrura are described. The descriptions were based on material collected from southwestern Java, Indonesia, Indian Ocean during the research cruise SJADES in 2018. The specimens were obtained using a box corer from lower bathyal depths of 836–2,355 m. These three genera are recorded from Southeast Asia for the first time.